Editorial JSE 24:3 - Braude, Stephen (Journal of Scientific Exploration, 2010)
The Journal of Scientific Exploration is devoted to the open-minded examination of scientific anomalies and other topics on the scientific frontier. Its articles and reviews, written by authorities in their respective fields, cover both data and theory in areas of science that are too often ignored or treated superficially by other scientific publications. This issue of the Journal features papers on a variety of subjects. The lead article discusses anomalous magnetic field activity during hands‑on healing and distant healing of mice with experimentally induced tumors. The next paper is a contribution to the growing body of research providing evidence of "presentiment," or an unconscious awareness of a future event. The article focuses specifically on the relationship between presentiment and psychological absorption. The third paper discusses striking similarities between two historical cases of remote viewing. In 1905, the Icelandic medium Indridi Indridason described in Reykjavik through a drop‑in‑communicator, a fire that was burning in Copenhagen. Similarly, in 1759, Emanuel Swedenborg described in Gothenburg a fire that raged near his home in Stockholm. The next article critically and meticulously examines, and challenges, the arguments in favor of concluding that the parapsychologist S. G. Soal falsified data in his well-known (and previously highly regarded) experiments in precognitive telepathy. The next paper considers which types of belief are beliefs in the paranormal. The authors identify various measures of paranormal belief and propose a nine-factor structure analysis of common paranormal belief dimensions. The final article is a fascinating account of some 1907 psychokinetic experiments with the medium Eusapia Palladino, conducted in Naples by Filippo Bottazzi. These experiments are particularly notable for having made instrumental recordings of the observed, ostensible PK movements. This issue of the JSE is then filled out, as usual, with correspondence and substantive book reviews.